Double trouble belowground: grapevine rootstocks face drought and copper toxicity - Fattorini, R.; Caretta, T. O.; Benyahia, F.; Zuluaga, M. Y. A.; Monterisi, S.; Agostini, A.; Andreotti, C.; Cesco, S.; Pii, Y. (Frontiers in Agronomy, 2025)
Background and aimsClimate change is intensifying abiotic stresses in viticulture, particularly through increased drought due to erratic rainfall. Meanwhile, copper (Cu2+) toxicity, a legacy of phytosanitary treatments, may be aggravated by these environmental shifts. This study evaluated the physiological and ionomic responses of young Vitis vinifera cv. Pinot gris plants, grafted onto three rootstocks (M4, 1103 Paulsen, SO4), under controlled drought, Cu2+ toxicity, and their combined effects.MethodsPlants were grown under greenhouse conditions and subjected to individual and combined stress treatments. Morpho-physiological traits, biomass distribution, and nutrient profiles were assessed to determine genotype-specific responses.ResultsDrought markedly reduced gas exchange and photosystem II efficiency (Fv/Fm), especially in SO4, while M4 maintained better physiological performance. Cu2+ toxicity alone had limited physiological impacts but significantly altered root ionomic profiles. Combined stress exacerbated water-state impairment, chlorophyll reduction, and nutrient imbalances, especially in SO4. The PCA analysis of ionomic data revealed clear separation of stress treatments among rootstocks, with M4 exhibiting the most distinct and balanced nutrient profile. In contrast, plants grafted on 1103 Paulsen and SO4 showed less coordinated nutrient responses and reduced recovery capacity.ConclusionsRootstock genotype strongly affected grapevine resilience under multifactorial stress. M4 emerged as the most tolerant, suggesting its suitability for future viticultural conditions marked by drought and soil contamination. These results emphasize the critical importance of belowground traits in selecting more resilient grapevine plants, integrating physiological and ionomic assessments, to enhance resilience against multifactorial stresses under climate change.